Performance of self consolidating concrete with recycled concrete aggregate / Mohd Afiq Mohd Fauzi - Mohd Fauzi, Mohd Afiq (2016)
Self Consolidating Concrete (SCC) is an emerging class of concrete materials that offers great potential for improved ease of positioning and scaled down cost through reduced time and labour. Generally, tonnes of Construction and Demolition Wastes (C&DW) are raised daily. The situation is similar to the paper industry where large amount of the wastes or paper sludge generated every day and at the same time bringing potential and devastating harmful impact to the surroundings. For this reason, the search into the use of coarse and fine recycled concrete aggregate produced from crushed concrete waste is looked into. Many researchers had found that waste materials have unique properties that could improve the quality of self consolidating concrete produced. Nevertheless, on that point there is no study available on using Waste Paper Sludge Ash (WPSA) as cement and coarse and fine Recycled Concrete Aggregate (RCA) as coarse and fine aggregate replacement materials respectively in self consolidating concrete. Therefore, the reuse of RCA and WPSA generated as the supplemental material for the replacement of aggregate and cement are significant in reducing the environmental impact. This research was focused on the strength characteristic and the chloride permeability level of SCC containing RCA and WPSA. The influence of RCA content in the range from 0% to 100% of Natural Aggregate (NA) to the strength characteristic and the chloride permeability level of SCC containing optimum WPSA was identified and compared with SCC containing normal mixes. In this research, three (3) series of concrete specimens were cast with different water cement ratios (0.53, 0.49 and 0.45). The concrete specimens were subjected to strength at the age of 3, 7, 14, 21, 28, 56 and 90 days and durability at the age of 28, 56 and 90 days. The result indicated that the compressive strength and chloride permeability of SCC containing 100% RCA replacement give better performance than the 0% RCA replacement. Based on the finding, SCC containing 100% RCA replacement can be categorized same as a conventional concrete hence it can be utilized for construction purposes. RCA can also acts as an alternative replacement in concrete for replacing the NA.